2013
DOI: 10.1073/pnas.1204109110
|View full text |Cite|
|
Sign up to set email alerts
|

Sensory adaptation as optimal resource allocation

Abstract: Fig. 1. The phylogenetic distribution of ABO phenotypes and genotypes. Shown is a phylogenetic tree of primate species, with a summary of phenotypic/ genotypic information given in the first column, and the genetic basis for the A versus B phenotype provided in the second column (functionally important codons at positions 266 and 268 are in uppercase letters). See Dataset S1 for the source of information about phenotypes/genotypes. Only species with available divergence times are represented here (34 of 40). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 52 publications
1
46
0
Order By: Relevance
“…Thus, contextual modulation may not necessarily impair all visually guided behavior, even if it alters neural and perceptual selectivity in a way that hinders behavioral performance on very specific and synthetic laboratory tasks. Gepshtein, Lesmes, and Albright (2013) recently demonstrated that adaptation, while detrimental under specific experimental conditions, actually represents an optimal allocation of sensory resources in the general case. Understanding contextual modulation's behavioral effects under naturalistic conditions may similarly prove to be a fruitful avenue for future research.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, contextual modulation may not necessarily impair all visually guided behavior, even if it alters neural and perceptual selectivity in a way that hinders behavioral performance on very specific and synthetic laboratory tasks. Gepshtein, Lesmes, and Albright (2013) recently demonstrated that adaptation, while detrimental under specific experimental conditions, actually represents an optimal allocation of sensory resources in the general case. Understanding contextual modulation's behavioral effects under naturalistic conditions may similarly prove to be a fruitful avenue for future research.…”
Section: Resultsmentioning
confidence: 99%
“…The overall approach of conceptualizing cognitive processes as optimization of neuronal resources has received experimental support and theoretical emphasis in the recent studies of visual perception (Gepshtein et al, 2013) and the analysis of candidate mechanisms in the brain capable of anticipation and long-term planning (“prospective optimization”; Sejnowski et al, 2014). Perhaps, the most compelling argument in favor of the present theory can be garnered from the work reported by Ito (1993, 2008), Salman (2002), Baillieux et al (2008); Ellis and Newton (2010), Murdoch (2010), and Rosenbloom et al (2012) suggesting a possibility that mental activities are controlled by internal models in the cerebellum (Ito, 2008), with movement and thought engaging identical control mechanisms (Ito, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…However, this was famously challenged by Stevens (35), who showed that the logarithmic-like behavior holds only at threshold. Weber-Fechner behavior for sensory attributes is now rarely interpreted to imply logarithmic encoding, usually adaptation or gain control, mechanisms that have been linked to optimal behavior (26,(36)(37)(38). So, the strongest evidence for logarithmic coding was the logarithmic numberline:…”
Section: Discussionmentioning
confidence: 99%